Rekayasa Sistem Informasi Penjualan Suku Cadang Menggunakan Metode Up Selling - Muhammad Amrin Lubis; Hesty Aisyah; R Rismayenti; S Suardinata; Rusli Saputra (Jurnal KomtekInfo, 2022)
Technological advances are always developing, especially in the field of utilizing computers both in terms of hardware and software. The use of technology in sales activities is expected to increase the number of sales and profits. Fauzan Motor store in its business activities still does not have an integrated system so that in running its business there are still many shortcomings such as the slow delivery of new products to customers, so that customers are only glued to one product. Lack of information obtained by customers causes low sales. Mala conducted this research for the Fauzan Motor store in increasing sales using the up selling method. The system built is a computerized sales system development. The system works by comparing the product that has been selected by the customer with similar products, such as a brand, category with a higher price and quality, one level above the product chosen by the customer. Sales information system development technique using the System Development Life Cycle (SDLC). The programming language used is PHP 7 which is based on Object Oriented Programming (OOP) and JavaScript. Structuring objects using Bootstrap 5 on web pages to make them more informative. This research produces a sales application system that can increase sales turnover. Each customer is given recommendations for several available products so that consumers can choose products according to quality and affordable prices. So this research is very helpful in increasing sales and is more effective in increasing store revenue.